Representation of women in form one literature in English for lower secondary schools / Siti Hindon Che Wok ...[et al.] - Che Wok, Siti Hindon; Ibrahim, Syazliyati; Mohammed, Syakirah; Versay Kudus, Nazima (Research Management Institute, 2010)
Women play multiple roles in different domains in a community. Nevertheless, the patriarchal structure of the society that has been deeply entrenched in the psychosocial settings of most communities in this world has made many women face a myriad of oppressive situations in their lives despite their importance. Such oppressions are also reflected in the literary texts. In the Malaysian context, different local fictions have been researched to uncover how the local women have been portrayed. However, in the literary texts which have been used in the literature component for secondary schools, their portrayal is still hidden since most studies conducted in this area have often been on how such texts can be exploited in the classroom. Hence, this study is meant to address the gap by looking at how women are actually represented in these texts. Texts highlighted are the three short stories for Form One Literature Component namely Of Bunga Telur and Bally Shoes, The Pencil and How Dalai Got Its Name. The framework chosen for study is feminist stylistics purported by Mills (1998). Findings indicate that generally women are portrayed rather negatively in all three levels of analysts which are at word, clause and discourse levels as exemplified by various excerpts quoted from the texts. Hence, since these texts are for the consumption of school students, several recommendations are made to correct the negative representations so that all students can benefit from the stories.